Bloodstream infections due to Trichosporon species in paediatric patients: Results from the first national study from Turkey - KEPENEKLİ KADAYİFCİ, EDA (Elsevier Masson s.r.l., 2022)
Background: Invasive Trichosporon infections are rarely seen opportunistic fungal infections in children and mainly affect immunocompromised patients. This multicenter retrospective study has rewieved the characteristics, risk factors, treatment modalities and outcomes of bloodstream infections caused by Trichosporon species in children diagnosed over the past ten years in Turkey. Methods: The study was performed with the participation of 12 of 55 hospitals invited from Turkey. In each center, the patients with bloodstream infections caused by Trichosporon spp. between January 2010 and December 2020 were retrospectively ascertained and the results were reported to the study coordinator by means of a simple case report. Data were collected on patient demographics, underlying condition(s), treatment of.infections caused by Trichosporon spp, and 7 and 30- day mortality rates. Results: A total of 28 cases with fungemia caused by Trichosporon spp. were included in the study. The most common underlying disease was paediatric cancers (39.3%). T. asahii infections were detected in 78.5 % (n=22) of patients. A various spectrum of antifungal treatment regimens were used including intravenous amphotericin B monotherapy in 35.7%, intravenous amphotericin B and voriconazole combination in 32.1% and intravenous voriconazole monotherapy in 28.6% of the patients. The overall mortality rate was 28.5 %. The mortality rates were 12.5% in the voricanozole, 30% in the amphotericin B and 33.3% in combined voriconazole -amphotericin B arms Conclusions: Invasive Trichosporon infections with an important impact of patients quality of life are almost related to underlying diseases with an overall mortality rate of 28.5%. Voriconazole was found to be associated with lower mortality rates when compared with other treatment regimens. © 2021 SFMM
Keywords: Invasive infection; paediatric; Trichosporon